1987
DOI: 10.1136/emj.4.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Deaths in three accident and emergency departments.

Abstract: SUMMARYA survey of three London hospitals found that approximately 045 patients per thousand new attenders die in the accident and emergency department and that there is evidence of poor management in about 10% of these deaths. The commonest faults were excessive delay before starting appropriate treatment and neglect of the basic principles of emergency medicine. These points need to be emphasized in the training of accident and emergency staff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…However, we found that mortalities in the 7 th and 8 th decades of life (61-80 years) resulted more from medical emergencies. This is in keeping with Beckett et al's report where 66% of deaths in three London EDs occurred in patients over 60 years (7). We report that while cerebrovascular accident was the major cause of medical emergency deaths in our environment, cardiac causes were predominant in Europe, the United States of America (USA) and some non-Western nations (1,3,7,(12)(13)(14).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…However, we found that mortalities in the 7 th and 8 th decades of life (61-80 years) resulted more from medical emergencies. This is in keeping with Beckett et al's report where 66% of deaths in three London EDs occurred in patients over 60 years (7). We report that while cerebrovascular accident was the major cause of medical emergency deaths in our environment, cardiac causes were predominant in Europe, the United States of America (USA) and some non-Western nations (1,3,7,(12)(13)(14).…”
Section: Resultssupporting
confidence: 91%
“…A breakdown of the mortality with respect to length of stay (LOS) in the ED showed that 283 (43.4%) deaths occurred within five Emergency Department Deaths (Figure). present in the ED requiring timely interventions, and using mortality rate as a measure of the quality of care, the high rates in our practice environment compared with 0.05-0.5% reported by researchers in advanced countries may highlight lack of pre-hospital care, poor infrastructure, absence of emergency transport system and ED staffed by untrained doctors and nurses, as contributory factors (7)(8)(9). The higher mortality rate in males compared with female patients in our audit followed the pattern reported by other studies (1, 3, 4, 8-10).…”
Section: Resultsmentioning
confidence: 99%
“… The observed mortality shows similar results to some previous studies. 7 , 13 Mortality among older patients is prevalent in the ED, and men are more vulnerable. The leading cause of death is cardiovascular disease, and the most common cardiovascular disease is AMI.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous surveys of deaths in accident and emergency departments in the UK (Shalley & Cross, 1984;Beckett et al, 1987) have included deaths from all causes. The London survey found that trauma deaths made up 13% of the total deaths occurring in three departments during one year and this is similar to our figure of 16% over a 5-year period.…”
Section: Discussionmentioning
confidence: 99%